Management of cardiogenic shock in patients with acute coronary syndromes. (2nd April 2019) - Rathod, Krishnaraj S; Sirker, Alexander; Baumbach, Andreas; Mathur, Anthony; Jones, Daniel A
Abstract : Cardiogenic shock remains a major problem affecting a large proportion of patients with acute coronary syndromes, with a persistent high mortality rate. Although mechanical reperfusion with percutaneous coronary intervention has improved outcomes following acute coronary syndromes, there is limited evidence supporting the other current treatments used to manage patients with cardiogenic shock (intra-aortic balloon pumps, percutaneous left ventricular assist devices and extracorporeal membrane oxygenation). This article looks at these options, assessing current evidence and recent advances. It also discusses areas that still require research to ensure there is improvement in these high-risk patients, such as coordinated regionalised approaches to cardiogenic shock management with multidisciplinary care provided in designated tertiary shock centres.